Early irrigation and agropastoralism at Mohuchahangoukou (MGK), Xinjiang, China. (December 2017) - Li, Yuqi; Storozum, Michael J.; Wang, Xin; Guo, Wu
Abstract: In Xinjiang, irrigation technology was fundamental to the mixed economy of local agropastoralists who were likely responsible for transmitting domesticated plants across Eurasia. However, a dearth of archaeological sites has long hindered archaeologists' efforts to understand the development of irrigation in Xinjiang. In this article, we present the results from our investigation of an archaeological site called Mohuchahangoukou (MGK), a recently discovered site in central Xinjiang with an irrigation system. We used drone-based photogrammetric surveys, pedestrian surveys, and test excavations to create a high-resolution map of a portion of this archaeological site to explore the architectural remains. In addition to identifying many houses and burials, we discovered a complicated irrigation system that consists of stone-constructed canals, check dams, cisterns, and fields. Our material analysis and radiocarbon dates place the construction of this irrigation system to the 3rd and 4th century CE. By comparing the irrigation system at MGK with other early irrigation systems found in Xinjiang, western Central Asia, and the Near East, we propose that the early irrigation technology that sustained the agropastoralist economy has probable roots in western Central Asia. The mechanism behind this technology transfer most likely was through networked interactions between agropastoralist communities that lived along the nearly continuous mountain chain extending from southern Central Asia to western China. Our discovery and analysis of MGK opens up new possibilities to examine the role irrigation played in developing agropastoralism in Central Asia and driving early trade and exchanges between western and eastern Eurasia.